Bistatic systems - Elminowicz, Andrzej; Zajączkowski, L. (Archives of Acoustics, 2006)
This paper describes key features of a bistatic operation in the hydroacoustic systems, his performance model and constraints imposed by environment and propagation conditions in shallow water. The architecture and construction of bistatic systems, their features and requirements has been presented. The application of bistatic systems, especially in protection systems, has been presented as barriers protecting anchorage or harbour, barriers protecting straits or entries to the harbour. Attention was paid on possibility of cooperation among existing, commonly available sonars and bistatic acoustics devices.